2021
DOI: 10.1002/ange.202102967
|View full text |Cite
|
Sign up to set email alerts
|

Highs and Lows of Bond Lengths: Is There Any Limit?

Abstract: Tw od istinct points on the potential energy curve (PEC) of apairwise interaction, the zero-energy crossing point and the point where the stretching force constant vanishes, allowu st oa nticipate the range of possible distances between two atoms in diatomic,m olecular moieties and crystalline systems.W es howt hat these bond-stability boundaries are unambiguously defined and correlate with topological descriptors of electron-density-based scalar fields,a nd can be calculated using generic PECs.C hemical datab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
5
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 81 publications
0
5
0
Order By: Relevance
“…A recent study [16] on pairwise interaction between atoms and its dependence on range of possible distances between the atoms demonstrated that the nature of interaction between H and O atom changes continuously with the distance between them. The authors of this study showed that as the distance between H and O atoms changed the nature of interatomic interaction gradually changed from primarily covalent in the range 0.58-1.36Å to primarily electrostatic in the range 1.36-2.14Å to primarily dispersive in the range 2.14-2.92Å, the authors predicted the occurrence of chained interactions of varying nature and strength between H and O atoms.…”
Section: Computation Methodsmentioning
confidence: 99%
“…A recent study [16] on pairwise interaction between atoms and its dependence on range of possible distances between the atoms demonstrated that the nature of interaction between H and O atom changes continuously with the distance between them. The authors of this study showed that as the distance between H and O atoms changed the nature of interatomic interaction gradually changed from primarily covalent in the range 0.58-1.36Å to primarily electrostatic in the range 1.36-2.14Å to primarily dispersive in the range 2.14-2.92Å, the authors predicted the occurrence of chained interactions of varying nature and strength between H and O atoms.…”
Section: Computation Methodsmentioning
confidence: 99%
“…On the theoretical side, based on atoms-in-molecules and electron localization function computations, Isea argued that C–C single bonds should still show key characteristics of sigma bonds up to ∼2.0 Å, but not beyond 2.0 Å . Based on the analysis of a large database, Lobato et al arrived at a similar conclusion recently . Based on careful temperature-dependent XRD analysis, Kubo et al interestingly noted that the intrinsic distance of the long C–C bond in 1 is somewhat shorter than 2.042 Å, close to ∼1.98 Å due to crystal packing effects.…”
Section: Introductionmentioning
confidence: 97%
“… 15 Based on the analysis of a large database, Lobato et al arrived at a similar conclusion recently. 16 Based on careful temperature-dependent XRD analysis, Kubo et al 1 interestingly noted that the intrinsic distance of the long C–C bond in 1 is somewhat shorter than 2.042 Å, close to ∼1.98 Å due to crystal packing effects. Cho et al 17 argued that this limit should be about 1.8 Å, slightly longer than suggested previously by Zavitsas 18 and Schreiner et al 8 based on the dependency of the binding energy as a function of the long C–C bond distance between two sp 3 carbon atoms connected to adamantanes or alkanes.…”
Section: Introductionmentioning
confidence: 99%
“…[7][8][9][10][11][12] Nonetheless, there are many systems (starting with H 2 ) where the existence of a chemical bond is not in doubt. Interestingly however, there does not appear to be a clear consensus on (and relatively little discussion of [13][14][15][16][17][18][19][20][21][22][23][24] ) where on the potential energy surface (PES) such bonds can be said to have been broken (or conversely, formed). This is somewhat unfortunate, as making/breaking bonds is key to chemical processes and is widely referenced in literature, often without accompanying definitions.…”
mentioning
confidence: 99%
“…It thus seems reasonable to target a quantity (preferably an observable) that has a maximum along the bond dissociation coordinate at a point which naturally separates the regime of shared electrons forming a bond from a regime corresponding to electron localization onto separate fragments. Such a property ideally ought to be electronic, and not some indirect influence of electronic structure on nuclei-dependent quantities like vibrational frequencies [18,23,24] or NMR chemical shifts. We propose the static polarizability (α) as such a property for a number of reasons, which we subsequently elaborate upon.…”
mentioning
confidence: 99%